26+3y-7=13y-11-4y

Since y is on the right side of the equation, switch the sides so it is on the left side of the equation.

13y-11-4y=26+3y-7

Subtract 4y from 13y.

9y-11=26+3y-7

Subtract 7 from 26.

9y-11=3y+19

Subtract 3y from both sides of the equation.

9y-11-3y=19

Subtract 3y from 9y.

6y-11=19

6y-11=19

Add 11 to both sides of the equation.

6y=19+11

Add 19 and 11.

6y=30

6y=30

Divide each term in 6y=30 by 6.

6y6=306

Cancel the common factor of 6.

Cancel the common factor.

6y6=306

Divide y by 1.

y=306

y=306

Divide 30 by 6.

y=5

y=5

Solve for y 26+3y-7=13y-11-4y